Prevalence of Adverse Health Effects of Tobacco Addiction in Different Types of Prakriti – An Observational Study: Life Sciences - Jagdish Mandhane, Rajat; Sawarkar, Dr. Gaurav; Sawarkar, Dr. Punam (International Journal of Life Science and Pharma Research, 2023)
According to the National Institute on Drug Abuse, tobacco is one of the most widely used addictive items in the United States (NIDA). Addiction is a long-term illness marked by obsessive drug seeking and usage and long-term chemical and molecular alterations in the brain. Tobacco smoking is linked to 5 million fatalities worldwide, making it one of the major causes of mortality. Comprehensive tobacco control programs can significantly lower the frequency of tobacco use. The study was a cross-sectional study. Approval was taken from the institutional ethical committee. Personal interviews were conducted at Mahatma Gandhi Ayurved College, Hospital & Research Centre, Salod (H), Wardha district. All the subjects were personally interviewed based on the questionnaire. The survey elicited 209 replies, and based on the findings, the following observations were made. Individuals who were addicted to tobacco chewing in the Wardha district were included in the study. One hundred percent of participants completed the survey. The evaluation used a question-and-answer format, a typical Prakriti assessment, and tobacco addiction-related questions. The study gathered 209 replies from tobacco-dependent residents in the Wardha district, who were selected based on their comments and observations. Tobacco chewing percentage was more found in males (21%) than females (2.8%). Twenty-five percent were primarily Vata Prakriti, fifty-nine percent were Pitta Prakriti, and eighteen percent were Kapha Prakriti. Compared to Pitta and Kapha Prakriti people, Vata-dominant Prakriti people are more likely to experience the negative effects of tobacco addiction.